Advances in echocardiography: insights into the mitral valve and implications for surgical and percutaneous repair. (December 2013) - Maffessanti, Francesco; Tamborini, Gloria; Fusini, Laura; Stevanella, Marco; Sotaquira, Miguel; Caiani, Enrico; Pepi, Mauro
New echocardiographic imaging modalities, mainly based on 3D data acquisition, have markedly improved our understanding of the normal and pathologic mitral valve mechanics. Qualitative and quantitative analysis of 3D data on the mitral valve could have a clinical impact on diagnosis, patient referral, and percutaneous and surgical strategies, as well as in the evaluation of the immediate and long-term surgical outcome. This review covers the contribution of new echocardiographic imaging modalities in the diagnosis of mitral valve disease, their role in selecting and monitoring percutaneous and surgical procedures, and in the assessment of procedural outcomes. Moreover, advantages versus the standard 2D modality, as well as future applications of advanced analysis techniques, will be presented.